The Implementation of the Qur'an Tahfidz Excellence Program at Senior High School - Hilwa Adenya Assyifatul Qolbi (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2025)
ENGLISH: The Implementation of the Qur'an Tahfidz Excellence Program at Senior High SchoolObjective: This study aims to analyze the implementation of the Qur'an Memorization Program at SMA Al Falah Ketintang Surabaya, focusing on its effectiveness and its impact on the students. Method: The approach used in this study is qualitative descriptive. Data was collected through interviews with the principal, vice principal for the curriculum, and the coordinator of the Qur'an Memorization Program, as well as through observations and analysis of documents related to the curriculum and school policies. Results: Implementing the Qur'an Memorization Program at SMA Al Falah Ketintang Surabaya has been successful for years, and a structured guideline, a conducive school environment, and efficient time management support it. Conclusion: The implementation of this program demonstrates an innovative approach to integrating Islamic values into the school curriculum and positively impacts the students' spiritual and academic development. Contribution: This study illustrates how Qur'an-based education can effectively function in formal schools and adds insight into the integration of analytical learning methods and technology in the memorization program, which can serve as a model for holistic education that combines Islamic values with academic skills. INDONESIAN: Implementasi Program Unggulan Tahfidz Al-Qur’an di SMATujuan: Tujuan: Penelitian ini bertujuan untuk menganalisis penerapan Program Tahfidz Al-Qur’an di SMA Al Falah Ketintang Surabaya, dengan fokus pada efektivitas pelaksanaannya serta dampaknya terhadap peserta didik. Metode: Pendekatan yang digunakan dalam penelitian ini adalah kualitatif deskriptif. Data dihimpun melalui wawancara dengan kepala sekolah, wakil kepala bagian kurikulum, dan koordinator guru program Tahfidz, observasi, serta analisis dokumen terkait kurikulum dan kebijakan sekolah. Hasil: Pelaksanaan Program Tahfidz Al-Qur’an di SMA Al Falah Ketintang Surabaya berjalan dengan baik selama bertahun-tahun, didukung oleh pedoman yang terstruktur, lingkungan sekolah yang kondusif, serta manajemen waktu yang efisien. Kesimpulan; Implementasi program ini menunjukkan pendekatan inovatif dalam mengintegrasikan nilai-nilai keislaman ke dalam kurikulum sekolah dan memberikan dampak positif pada perkembangan spiritual dan akademik siswa. Kontribusi: Penelitian ini memberikan kontribusi dalam menggambarkan bagaimana pendidikan berbasis Al-Qur’an dapat berjalan efektif di sekolah formal, serta menambah wawasan terkait integrasi metode pembelajaran analitis dan teknologi dalam program tahfidz, yang dapat dijadikan model pendidikan holistik yang menggabungkan nilai-nilai keislaman dengan keterampilan akademik.